2020
DOI: 10.1111/joim.13020
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk after three bariatric surgery procedures in Swedish obese subjects: up to 26 years follow‐up of a controlled intervention study

Abstract: Ahlin S, Peltonen M, Sj€ oholm K, Anveden A, Jacobson P, Andersson-Assarsson JC, Taube M, Larsson I, Lohmander LS, N€ aslund I, Svensson P-A, Carlsson LMS ). Fracture risk after three bariatric surgery procedures in Swedish obese subjects: up to 26 years follow-up of a controlled intervention study. J Intern Med 2020; 287: 546-557.Background. Previous studies have reported an increased fracture risk after bariatric surgery.Objective. To investigate the association between different bariatric surgery procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 41 publications
1
52
0
2
Order By: Relevance
“…Two studies compared the gastric bypass procedure with a restrictive procedure such as gastric banding. In these, bypass seemed to carry a greater risk for osteoporotic fractures such as hip fractures, as well as wrist fractures [15,17]. Reduction in bone mineral density does not fully explain the occurrence of wrist fractures; other risk factors could be involved including lower grip strength, increased walking speed, and increased risk for a fall outdoors [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies compared the gastric bypass procedure with a restrictive procedure such as gastric banding. In these, bypass seemed to carry a greater risk for osteoporotic fractures such as hip fractures, as well as wrist fractures [15,17]. Reduction in bone mineral density does not fully explain the occurrence of wrist fractures; other risk factors could be involved including lower grip strength, increased walking speed, and increased risk for a fall outdoors [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric procedures, in particular those based on malabsorption, lead to a fall in bone mineral density (BMD) [9][10][11][12], an increase in bone resorption and bone remodeling, and changes in bone histomorphometry parameters [10,13,14]. The risk for fracture increases at several skeletal sites after bariatric surgery [15][16][17]. These changes in bone metabolism seem not to be the result of weight loss alone, since BMD continues to decline even when the patient's weight has stabilized [18].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis, the highest possibility of fracture was found after malabsortive procedures (biliopancreatic diversion) followed by the mixed techniques (RYGB) without an increased risk after restrictive procedures (adjustable gastric banding and SG) compared to the nonsurgical population [64]. Recently, the 26 year results of the S.O.S study [65] observed the highest incidence rate for first fracture after RYGB compared to restrictive procedures. In our cohort, the small size and time of observation were probably the reason why we had no bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients are advised to take lifelong vitamin D and calcium supplementation to counteract this, albeit the long-term efficacy of the prevention has still not been established. Several reports during the last years have shown negative effects of RYGB on bone mineralization, and now recently even indicate an increased risk of osteoporotic fractures, despite the supplementation therapy, which suggests that the supplementation is not effective in preventing the decreased calcium absorption and in the long-run osteoporosis ( Yu et al, 2017 ; Rousseau et al, 2016 ; Axelsson et al, 2018 ; Ahlin et al, 2020 ). It was recently reported that RYGB leads to an up to almost 80% decreased fractional calcium absorption, despite adequate vitamin D levels ( Schafer, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that RYGB leads to an up to almost 80% decreased fractional calcium absorption, despite adequate vitamin D levels ( Schafer, 2017 ). It has also been shown that the risk of osteoporotic fractures is increased in particular after RYGB more than other bariatric surgery methods, and is thus not only a consequence of the weight decrease ( Rousseau et al, 2016 ; Ahlin et al, 2020 ; Nakamura et al, 2014 ; Lu et al, 2015 ). Therefore, it is of importance to try finding mechanisms that can explain this effect, and make it possible to find treatments to reverse the decreased calcium absorption after RYGB.…”
Section: Introductionmentioning
confidence: 99%